Phytate/calcium molar ratio does not predict accessibility of calcium in ready‐to‐eat dishes. (25th January 2017) - Erba, Daniela; Manini, Federica; Meroni, Erika; Casiraghi, Maria C
Abstract: BACKGROUND: Phytic acid (PA), a naturally occurring compound of plant food, is generally considered to affect mineral bioavailability. The aim of this study was to investigate the reliability of the PA/calcium molar ratio as a predictive factor of calcium accessibility in composed dishes and their ingredients. RESULTS: Dishes were chosen whose ingredients were rich in Ca (milk or cheese) or in PA (whole‐wheat cereals) in order to consider a range of PA/Ca ratios (from 0 to 2.4) and measure Ca solubility using an in vitro approach. The amounts of soluble Ca in composed dishes were consistent with the sum of soluble Ca from ingredients (three out of five meals) or higher. Among whole‐wheat products, bread showed higher Ca accessibility (71%, PA/Ca = 1.1) than biscuits (23%, PA/Ca = 0.9) and pasta (15%, PA/Ca = 1.5), and among Ca‐rich ingredients, semi‐skimmed milk displayed higher Ca accessibility (64%) than sliced cheese (50%) and Parmesan (38%). No significant correlation between the PA/Ca ratio and Ca accessibility was found ( P = 0.077). CONCLUSION: The reliability of the PA/Ca ratio for predicting the availability of calcium in composed dishes is unsatisfactory; data emphasized the importance of the overall food matrix influence on mineral accessibility. © 2016 Society of Chemical Industry